Naturalization and the Rights of Citizens (American Journal of Islam and Society, 1994)
The subject of naturalization, which is an integml part of the conceptof identity and its related problems, has been an issue in the Muslimworld since its filst contacts with western thought, culture, military, andpolitics. Even though the matter was decided, in practical terms, by theemergence of ethnic and geographic nation-states out of the wreckage ofthe Ottoman Empire, it remains an open topic at the cultural and academiclevels. In fact, whether it is addressed as a challenge, an excuse,or as a means to an end, it remains a major and very sensitive question.As new ethnic and regional Muslim nation-states begin to show signs ofinstability, the subject grows more complex: it takes on new aspects ofidentity and affiliation and seeks to discover the best way of ordering relationsbetween the peoples of each region or between them and the (factional,military, or otherwise) elitist governments controlling them.With the stirrings of a new Islamic movement and its members' beliefthat Islam represents a viable political alternative, the question of naturalizationhas become a major challenge to them. In fact, it is often thrownin their faces by their secularist opponents. Thus the question has becomeinstrumental in the current political struggle taking place in the Islamicworld. Many Muslim governments cite indigenous non-Muslim minoritiesas an excuse to deprive their Muslim majorities, who often represent 98percent of the total population, of the right to be ruled by the Shari'ah.These are the same governments that discredit Islamic movements byviewing their very presence, principles, demands, and objectives as athreat to national unity. To counteract this "threat," then, they promulgate"emergency measures" and suspend constitutional legal codes.Naturalization is the basis of nationalism, which gives identity to themodem state, and may be defined as an affiliation with a geographicallydefined region. Anyone who traces hisher lineage to that region is subjectto all accompanying rights and responsibilities. Thus the bond betweenthem is secular and worldly. The same is true of bonds betweenstates, for they are entirely secular and m e a s d in terms of profit andloss. It is essential that all citizens, regardless of their religious, ethnic or ...